In Vitro Antifungal Activity and Toxicity of Dihydrocarvone-Hybrid Derivatives against Monilinia fructicola - Díaz, Katy (Antibiotics (Basel), 2021)
The aim of this study was to synthesize a series of novel and known dihydrocarvone-hybrid derivatives (2–9) and to evaluate mycelial growth activity of hybrid molecules against two strains of Monilinia fructicola, as well as their toxicity. Dihydrocarvone-hybrid derivatives have been synthesized under sonication conditions and characterized by FTIR, NMR, and HRMS. Antifungal efficacy against both strains of M. fructicola was determined by half maximal effective concentration (EC(50)) and toxicity using the brine shrimp lethality test (BSLT). Among the synthesized compounds, 7 and 8 showed the best activity against both strains of M. fructicola with EC(50) values of 148.1 and 145.9 µg/mL for strain 1 and 18.1 and 15.7 µg/mL for strain 2, respectively, compared to BC 1000(®) (commercial organic fungicide) but lower than Mystic(®) 520 SC. However, these compounds showed low toxicity values, 910 and 890 µg/mL, respectively, compared to Mystic(®) 520 SC, which was highly toxic. Based on the results, these hybrid compounds could be considered for the development of more active, less toxic, and environmentally friendly antifungal agents against phytopathogenic fungi.